Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2023)
Number of pages: 12

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2023)
Number of pages: 10

Community NetLink - Community Health and Social Services Network (CHSSN) (2023)
Number of pages: 12

Community NetLink - Community Health and Social Services Network (CHSSN) (2023)
Number of pages: 10

Faits saillants : Enquête sur la vulnérabilité des pères d'expression anglaise - Community Health and Social Services Network (CHSSN) (2022)

Sondage Youth Pulse Check : Principales conclusions - Community Health and Social Services Network (CHSSN) (2022)

Survey Highlights on the Vulnerability of English-speaking Fathers - Community Health and Social Services Network (CHSSN) (2022)

Youth Pulse Check Survey : Key Findings - Community Health and Social Services Network (CHSSN) (2022)

Sondage Youth Pulse Check : Rapport des résultats du sondage - Nigam, Sunita (Community Health and Social Services Network (CHSSN), 2022)
This document outlines the most important findings of the Youth Pulse Check, a mental health survey filled out by 456 English-speaking youth between the ages of 18-29 from 14 regions across the province of Quebec. Although 90% of respondents said they struggled at least somewhat often with their mental wellbeing and 81% of respondents, said that the COVID-19 pandemic has increased their struggles to feel well at a level 3 or more on a scale of 1 to 5, the survey revealed that many English-speaking youth feel there are significant gaps and barriers in accessing mental health services in their region. If many youth reported having sought out help in the past without success—meeting with barriers such as long wait lists, the prohibitive costs of mental health support, or the unavailability of services in English— other youth reported not having sought out help because of a lack of information about services to which they might turn.

Youth Pulse Check : Survey Results Report - Nigam, Sunita (Community Health and Social Services Network (CHSSN), 2022)
This document outlines the most important findings of the Youth Pulse Check, a mental health survey filled out by 456 English-speaking youth between the ages of 18-29 from 14 regions across the province of Quebec. Although 90% of respondents said they struggled at least somewhat often with their mental wellbeing and 81% of respondents, said that the COVID-19 pandemic has increased their struggles to feel well at a level 3 or more on a scale of 1 to 5, the survey revealed that many English-speaking youth feel there are significant gaps and barriers in accessing mental health services in their region. If many youth reported having sought out help in the past without success—meeting with barriers such as long wait lists, the prohibitive costs of mental health support, or the unavailability of services in English— other youth reported not having sought out help because of a lack of information about services to which they might turn.

CHSSN Montreal Community Forum : Mental Health and COVID-19 - Community Health and Social Services Network (CHSSN) (2021)
The forum brought together representatives from the provincial government, the health sector, the community, various research initiatives, and leaders from across the Island of Montreal to discuss the effects of COVID-19 on mental health for English speakers living on the Island. The event also served as a platform forcelebrating the successes of different mental health initiatives and for co-generating solutions to some of the most urgent problems facing mental health amongst English speakers in the context of COVID-19. With the goal of deepening an understanding of the impact of COVID-19 on different demographic segments of the English-speaking population of Montreal, CHSSN invited speakers working with a wide range of populations and possessing diverse lived experiences of the pandemic. The forum was designed to foster cross-sectoral and intersectional exchanges and to create a space for learning, discovery, consciousness-raising, resource-sharing, networking, and collaborating.

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2021)
Number of pages: 10

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de l'Ouest-de-l'Île de Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2019)
Number of pages: 10